2006
DOI: 10.1200/jco.2005.05.0245
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Advanced Gastric Cancer: A Systematic Review and Meta-Analysis Based on Aggregate Data

Abstract: Best survival results are achieved with three-drug regimens containing FU, an anthracycline, and cisplatin. Among these, regimens including FU as bolus exhibit a higher rate of toxic deaths than regimens using a continuous infusion of FU, such as epirubicin, cisplatin, and continuous-infusion FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
706
2
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,056 publications
(752 citation statements)
references
References 38 publications
15
706
2
15
Order By: Relevance
“…The overall response rate (45.2%), median TTP (5.7 months), and median overall survival (9.9 months) following treatment with the present regimen were comparable with previous results reported for cisplatin-based combinations (Boku et al, 1999;Roth et al, 2000;Vanhoefer et al, 2001), where a continuous infusion of a 5-flourouracil (5-FU) and cisplatin regimen achieved a response rate of 51% and median TTP of 5.45 months (Vanhoefer et al, 2001), while docetaxel plus cisplatin regimens achieved a response rate and median TTP of 48% and 6.6 months, respectively (Roth et al, 2000). However, in a recent meta-analysis of randomised phase II and phase III studies best survival results were achieved with three-drug regimens containing 5-FU, an anthracycline, and cisplatin in patients with advanced gastric cancer (Wagner et al, 2006). Oxaliplatin, which is commonly used in the treatment of colorectal cancer, has also been shown to be active and safe in the treatment of locally advanced or metastatic gastric cancer (Louvet et al, 2002;Al-Batran et al, 2004;Suh et al, 2005;Park et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate (45.2%), median TTP (5.7 months), and median overall survival (9.9 months) following treatment with the present regimen were comparable with previous results reported for cisplatin-based combinations (Boku et al, 1999;Roth et al, 2000;Vanhoefer et al, 2001), where a continuous infusion of a 5-flourouracil (5-FU) and cisplatin regimen achieved a response rate of 51% and median TTP of 5.45 months (Vanhoefer et al, 2001), while docetaxel plus cisplatin regimens achieved a response rate and median TTP of 48% and 6.6 months, respectively (Roth et al, 2000). However, in a recent meta-analysis of randomised phase II and phase III studies best survival results were achieved with three-drug regimens containing 5-FU, an anthracycline, and cisplatin in patients with advanced gastric cancer (Wagner et al, 2006). Oxaliplatin, which is commonly used in the treatment of colorectal cancer, has also been shown to be active and safe in the treatment of locally advanced or metastatic gastric cancer (Louvet et al, 2002;Al-Batran et al, 2004;Suh et al, 2005;Park et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies comparing polychemotherapy to single-agent treatment showed a significant gain in median survival with combination therapy establishing its role in the palliative setting [4]. A number of different chemotherapy combination regimens has been developed using the most active agents in advanced and metastatic gastric cancer without establishing a universally accepted standard regimen [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the combination of 5-fluorouracil (5-FU) and cisplatin remains an accepted treatment option for this disease [6] both in Europe and North America. The addition of an anthracycline is a widely accepted option since a meta-analysis [4] that compared 5-FU/cisplatin-containing regimens with versus without anthracyclines (HR = 0.77, 95% CI 0.62-0.95) showed a significant (but relatively small) survival benefit for the three-drug combination.…”
Section: Introductionmentioning
confidence: 99%
“…In metastatic patients, chemotherapy may provide a substantial palliation, and can improve survival and quality of life compared to best supportive care [2], and Xuorouracil, alone or associated with folinic acid, represents the cornerstone for the treatment of this disease [2]. A recent meta-analysis showed that combination regimens achieve better survival outcomes than Xuorouracil monotherapy, and that regimens containing Xuorouracil, anthracyclines and cisplatin are the most eVective [3]. Indeed, epirubicin, cisplatin and infusional Xuorouracil (ECF) regimen is one of the most widely used in Europe, while in US the standard regimen has remained for a long time cisplatin and infusional Xuorouracil (CF) [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%